17. századi disputáció-tiszteletpéldányok a Sárospataki Református Kollégium Nagykönyvtárában - Gábor ÉGER (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
Dedicated Complimentary Copies of 17th-Century Disputations in the Great Library of the Sárospatak Reformed College. In the 17th century, Hungarian Calvinist students in the universities of Germany and the Netherlands held numerous scholarly disputations on medical, philosophical, and theological topics. The Great Library of the Sárospatak Reformed College has several hundred works of this kind in its collections. Many of these are unique copies, and the special feature of many of them are the annotations on the title pages or on the last page, which contain the dedication of the respondent and inform about the sending of a complimentary copy. The Great Library of Sárospatak owns seven composite volumes with a lot of entries. The following students have received dedicated disputations from their fellow students: Jakab Alistáli Farkas, Pál Diószegi Kalmár, Ferenc Domjáni, András Egrespataki, Tamás Lévai Suba, Márton Dús Muraközi, István Szikszai D., András Tarpai Szilágyi, and Mihály Tatai P., to whom their friends in peregrination and former schoolfellows in Hungarian and Transylvanian colleges sent their published dissertations. The thirty-seven dedicated disputations provide insight into the network of relationships of the university students who studied abroad in the early modern period. And entries sometimes demonstrate close friendships and examples of respect towards each other and the signs of recognition.